(untitled) (Comprehensive Journal of Science, 2025)
The research "The Role of Youth in Economic and Social Development" addresses the importance of youth as a pivotal category in promoting growth and development in societies. The research highlights that youth represent a large percentage of the population, which gives them the ability to influence various fields. It indicates that youth participation in the economy, whether through work or entrepreneurship, contributes to achieving sustainable development. The research also addresses the role of youth in promoting social change through active participation in community and political activities, which contributes to building a more cohesive society. It also discusses the challenges facing youth, such as unemployment and lack of opportunities, and how they can be overcome through education and training. In addition, the research reviews strategies for activating the role of youth in development, such as creating platforms to support innovation and youth initiatives, and the importance of partnerships between the public and private sectors. Finally, the research emphasizes the need to invest in the energies of youth and provide the appropriate environment to enable them to contribute effectively to economic and social development.